Konduktivitas Fluida-Cairan Di Manifestasi Panas Bumi Bukit Kasih Kanonang Sulawesi Utara - H Taunaumang; P E Golioth (Universitas Negeri Malang, 2017)
Research on characteristics of fluid-liquid at hot spring water manifestation of Bukit Kasih Kanonang, Kabupaten Minahasa, North Sulawesi have been carried out. The hot spring water manifestation of the Bukit Kasih Kanonang has been known as one of natural tourism object in North Sulawesi. However, the fluid-liquid characterstics at this manifestation location are not yet identified. The aim of this research is to know the chemistry element composition in the fluid-liquid at the hot spring water manifestion Bukit Kasih Kanong and also physical properties such as conductivity and temperature of the fluid-liquid. This research result is very important information for the North Sulawesi community or tourist who visiting this location. The identification the element composition in the fluid-liquid has been measured by using XRF (X-Ray fluorescence spectrometry). And the conductivity and pH were measured using Prolab 2000 Schott Instruments. The experimental results of conductivity measurement and pH, and temperature of fluid-liquid in the three manifestation location are discussed in this article. The experimental result shows that, the pH value of the fluid-liquid in the manifestion location is categorized as strong electrolit acid. The conductivity value of fluid-liquid is depent on its pH value. And the pH value is strongly determined by the Cloride acid composition which dissociates in the fluid-liquid.DOI: http://dx.doi.org/10.17977/um024v2i12017p029